2016
DOI: 10.5624/isd.2016.46.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the priority of anatomic structures according to the diagnostic task in cone-beam computed tomographic images

Abstract: PurposeThis study was designed to evaluate differences in the required visibility of anatomic structures according to the diagnostic tasks of implant planning and periapical diagnosis.Materials and MethodsImages of a real skull phantom were acquired under 24 combinations of different exposure conditions in a cone-beam computed tomography scanner (60, 70, 80, 90, 100, and 110 kV and 4, 6, 8, and 10 mA). Five radiologists evaluated the visibility of anatomic structures and the image quality for diagnostic tasks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Diverse results have been reported, depending on the criteria used to evaluate image quality, devices, exposure parameters, and the amount of dose reduction. Most studies have found that a considerable dose reduction using exposure parameters below manufacturers' default settings is possible with the image quality remaining adequate 2425262728293031. The results of this study support those results, as changes in the tube current showed a significant effect on image quality.…”
Section: Discussionsupporting
confidence: 81%
“…Diverse results have been reported, depending on the criteria used to evaluate image quality, devices, exposure parameters, and the amount of dose reduction. Most studies have found that a considerable dose reduction using exposure parameters below manufacturers' default settings is possible with the image quality remaining adequate 2425262728293031. The results of this study support those results, as changes in the tube current showed a significant effect on image quality.…”
Section: Discussionsupporting
confidence: 81%
“…We used two phantoms of human skulls encased in acrylic articulated for medical use (Erler Zimmer Co., Lauf, Germany), one with and the other without metal restorations causing streak artifacts. The phantoms have been used in our previous studies 45 48 . The images of the phantoms were obtained with a MDCT (Somatom Sensation 10, Siemens AG, Erlangen, Germany) and a CBCT (CS 9300, Carestream Health, Inc., Rochester, US), respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Although the gold standard for image quality is a subjective evaluation of whether it is appropriate for clinical purposes, quantitative measurements of physical factors are useful for optimization, quality control, and performance evaluation 2311. MTF values are a useful quantitative factor for evaluating spatial resolution.…”
Section: Discussionmentioning
confidence: 99%